The Relationship between Art and Education : Analytical Study (Raparin Journal of Humanities (RJH), 2023)
Art and education are two main significant subjects. They have had a great effect on both Man's life and thinking in past and their effects in present which are seen obviously yet nowadays.Indeed, as two different independent fields, each of them has its own independent concept, task and indication as well as there is a strong connection between them at the same time. As it can be seen and sensed their effective roles in Man's life and thinking clearly in different ways, in the same way, their connections are obvious and it has been reached a level that makes a new independent philosophical ideological field come into being which is (Education of Art).            Art is a way of using of imagination to express idea through the various kinds of arts such as: music, drawing and painting, performance, literature, sculpture or any other subject in the field. According to different eras, philosophies and understandings; art has a different indication and meaning. In giving importance on the concept of art, it has been different form an era and a philosophy to an era and philosophy in different times and it can be seen that its significance is different clearly.            In the same way, education is a really important subject and Man has given importance to it from pre-historic era for the purpose of directing, instructing, teaching and educating a person or a thing so as to adapt with a various environment and different elements until the final stage which is endurable.            The significance and key role of this field has been noticed and seen in different ways throughout history. Although, each of art and education has relation with each other and they have influence on each other, at the same time, each of them has relationship with other sciences in different ways. Because, these two subjects are not closed subjects in the face of other fields like knowledge, thinking and public life. These connections are clearly appeared in fields of sociology, religion, science, ethics, psychology and nature.            The relationship between art and education is more appeared in the education of children. The educators demand to get benefit from art to improve and ease the process of education, at the same time, it is given importance to education in order to teach different kinds of arts.